The Necessary Core Competitiveness Training of College Graduates in the Workplace - Xu Yandi (SHS Web of Conferences)
The difficulty of college graduates in finding jobs has been widely discussed, but there are still many problems in how to prevent college graduates from being unable to find suitable jobs. This analyzes the specific difficulties of college students looking for jobs and the core competitiveness that needs to be improved. Through the research and investigation of the market, it is found that the problem of fresh graduates surviving in finding a job is not only that there are too many applicants in the market objectively, but also subjectively reflects that in the process of linking the school and the market, students do not acquire the corresponding ability to show themselves. Based on such an analysis, this essay analyzes and concludes that learning ability, practical ability, irreplaceability, and positive attitude towards work are very key elements and proposes to integrate these four elements into the education process during undergraduate study.